Dark Matter of Primate Genomes: Satellite DNA Repeats and Their Evolutionary Dynamics - Ahmad, Syed Farhan (2020)
A substantial portion of the primate genome is composed of non-coding regions, so-called dark matter, which includes an abundance of tandemly repeated sequences called satellite DNA. Collectively known as the satellitome, this genomic component offers exciting evolutionary insights into aspects of primate genome biology that raise new questions and challenge existing paradigms. A complete human reference genome was recently reported with telomere-to-telomere human X chromosome assembly that resolved hundreds of dark regions, encompassing a 3.1 Mb centromeric satellite array that had not been identified previously. With the recent exponential increase in the availability of primate genomes, and the development of modern genomic and bioinformatics tools, extensive growth in our knowledge concerning the structure, function, and evolution of satellite elements is expected. The current state of knowledge on this topic is summarized, highlighting various types of primate-specific satellite repeats to compare their proportions across diverse lineages. Inter- and intraspecific variation of satellite repeats in the primate genome are reviewed. The functional significance of these sequences is discussed by describing how the transcriptional activity of satellite repeats can affect gene expression during different cellular processes. Sex-linked satellites are outlined, together with their respective genomic organization. Mechanisms are proposed whereby satellite repeats might have emerged as novel sequences during different evolutionary phases. Finally, the main challenges that hinder the detection of satellite DNA are outlined and an overview of the latest methodologies to address technological limitations is presented.